Heating power and heating energy effect on the thermal runaway propagation characteristics of lithium-ion battery module: Experiments and modeling. (15th April 2022) - Jin, Changyong; Sun, Yuedong; Wang, Huaibin; Zheng, Yuejiu; Wang, Shuyu; Rui, Xinyu; Xu, Chengshan; Feng, Xuning; Wang, Hewu; Ouyang, Minggao
Highlights: Thermal runaway propagation tests with seven different heating powers are conducted. Energy flow of battery module during thermal runaway propagation is analyzed. Mechanism of thermal runaway triggered by external heating is revealed: the accumulation of heat energy. Accelerated thermal runaway propagation phenomenon caused by pre-heating effect is discovered. Recommended heating power for thermal runaway propagation tests is given out. Abstract: External heating was considered the best repeatable triggering method in thermal runaway propagation test. This paper investigates the effects of heating power and heating energy on the thermal runaway propagation characteristics of lithium-ion battery modules through both experiments and simulations. Thermal propagation tests were conducted with seven different heating powers, and the correlated models were built and calibrated by the test results. For both the simulations and experiments, propagation time intervals between adjacent batteries under thermal runaway sequence are extracted and compared. The energy flow of four critical heat transfer interfaces in a battery module was analyzed, the mechanism of thermal runaway triggered by external heating is revealed: the accumulation of heat energy. Through the analysis of 3D temperature distributions of the module before the first battery thermal runaway, the pre-heating effect, was discovered and was regarded as the primary cause of acceleration of TRP time interval. The pre-heating effect can help to reveal the other circumstances that lead to TRP acceleration. The energy flow under higher heating powers is compared with battery's TR, allowing the selection of the appropriate triggering heating power for the thermal runaway propagation test. The model-based tool of battery safety saves time and cost during research and development, supporting the technical issues for making reasonable tests. And it is important to understand the model-based tool in predicting the thermal runaway behavior of the battery module.